2022
DOI: 10.25299/jshmic.2022.vol9(1).9036
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Indonesian-Eglish Code Mixing Used in Social Media (TWITTER)

Abstract: This study entitled An Analysis of Indonesian-English Code Mixing on Social Media was examined by the researcher (Twitter). The goal of this study is to determine the form and function of Indonesian-English code-mixing on Twitter. A descriptive qualitative method was used to perform this study. The data for this study employed the tweets of influential people on Twitter. The instrument utilized by this researcher was documentation. This study was carried out entirely online, primarily on Twitter. The influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Habit also becomes the reason why they often use code mixing as well. Nabila (2021) in her research entitled "An Analysis of Indonesian-English Code Mixing Used in social media (Twitter). The result told that six forms of code mixing found in Twitter, as follows: 53 data found in code mixing of word, code mixing of phrase 20 data, 8 data in code mixing of hybrid, code mixing of word repetition 1 data, 7 data in code mixing of idiom, and 25 data found in code mixing of clause.…”
Section: Introductionmentioning
confidence: 99%
“…Habit also becomes the reason why they often use code mixing as well. Nabila (2021) in her research entitled "An Analysis of Indonesian-English Code Mixing Used in social media (Twitter). The result told that six forms of code mixing found in Twitter, as follows: 53 data found in code mixing of word, code mixing of phrase 20 data, 8 data in code mixing of hybrid, code mixing of word repetition 1 data, 7 data in code mixing of idiom, and 25 data found in code mixing of clause.…”
Section: Introductionmentioning
confidence: 99%
“…The study also revealed that Sheryl's followers used code-mixing to express Dominance Attitude and Language Attitude. Another noteworthy study by Cindy Nabila and Andi Idayani (2022) from Islamic University Riau, "An Analysis of Indonesian-English Code Mixing Used in Social Media (Twitter)," utilized tweets from prominent Twitter personalities as the primary data source. Through documentation, the researchers analyzed these tweets and identified significant motivations for code-mixing on Twitter, including the desire for motivation, knowledge enhancement, humor, and emotional expression.…”
Section: Introductionmentioning
confidence: 99%
“…And the results of their research in the types intra-sentential code-mixing, intra-lexical code-mixing, and involving change of pronunciation. And for the last, the researchers taken from (Nabila & Idayani, 2022). In this study, the researchers analyzed about forms of code-mixing used in social media.…”
Section: Introductionmentioning
confidence: 99%